Analisis Kesulitan Belajar Siswa Dalam Pemecahan Masalah Matematis Pada Materi Peluang - Wardah Saniyah; Fitri Alyani (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
The purpose of this research is to analyze students' learning difficulties in solving mathematical problems on the material of opportunity. There are several indicators contained in mathematical problem solving abilities, namely understanding the problem, planning a solution, implementing the plan,  and re-examining the process and results. The subjects in this study were students from SMP/MTs equivalent in the city of Jakarta, totaling 121 students. The researcher used a qualitative descriptive research method. The instrument tested in this study is a mathematical problem solving ability test with 5 description questions related to the material opportunity. Google form is used as a data collection technique to test mathematical problem solving abilities. The research data was obtained using the Winsteps application and then analyzed using the Rasch model. The results of data analysis in this study indicate that there are students' learning difficulties in solving mathematical problems on the material of opportunity, which is contained in the indicator of planning a settlement (Devising a plan), where students are not able to formulate mathematical problems or develop mathematical models on the problems given opportunities.